POTENTIAL ANALYSIS OF BUILDING INFORMATION MODELING IMPLEMENTATION IN INDONESIAN CONSTRUCTION INDUSTRY - Gradiyanto Gustaf, Felix
Building Information Modeling is a high-end technology which has begun attaining its spotlight especially in AEC (Architectural, Engineering, and Construction) industry due to its availability in producing a detailed and precise design that has a huge benefit during a whole project life cycle. The development of the BIM implementation in construction industry has reached the global scale including Indonesia. Nowadays, plenty of construction industries practicians such as governments, owners, consultants/constractors, and universities/institutes has started to realize the importance of BIM and begun to use it in the industry. Therefore, this research is aiming to acquire the potential BIM utilization mapping while simultaneously overseeing any issues which are likely to happen. BIM utilization mapping is a knowledge and realization level of the respondent about BIM in construction industry in Indonesia. The methodology which is used to achieve that target is both empirical and inductive which are directly derived out of the surveys results. Survey instrument that is used is questionnaire based method whose data will be processed using the descriptive statistic and comparison. From both methods, there are two conclusions acquired such as: (1) Construction industry in Indonesia has a high potential if it is seen through the high value of knowledge and realization level of every individual and organization which stay in the initial stage, (2) The most potential issues in adopting BIM in Indonesia consecutively are software and the training fees, experts lacking, less-awareness of BIM, lacks of the supporting environment in BIM utilization, unavailability of BIM tutorials books and guides, unintentional attitudes towards changes and no demand in using BIM through the construction industry itself.